Saberes bioculturais: plantas medicinais dos quintais periurbanos no município de São Paulo de Olivença, AM - Pereira, Ana Beatriz Sebastião (Brasil, 2024)
Biocultural knowledge originates from very important healing practices in the Amazon region, which, due to the region's geographical difficulties, constitute alternatives for treating diseases. In this sense, the peri-urban backyards of small cities in the interior of Amazonas are important, because they constitute the natural capital formed by areas that have a diverse flora, managed and cultivated by residents, used in different ways and for various therapeutic indications. This research aims to understand the social, economic, environmental and cultural relevance that the cultivation of medicinal species symbolizes for residents of the municipality of São Paulo de Olivença, AM. It fits the descriptive type, with a qualitative approach. The development of this work was carried out in the neighborhood of Colônia São Sebastião, Jordan and São Joaquim of that municipality. The data collection instrument was through interviews with residents who cultivate medicinal plants in their backyards using the “snowball” method. The data obtained was tabulated in an Excel spreadsheet to generate tables and graphs and through this it was possible to verify that the biocultural knowledge of the population is important to maintain the culture of using medicinal plants. A total of 40 ethnospecies of medicinal plants grouped together in 26 different botanical families were identified in the three neighborhoods of São Paulo de Olivença, AM. Therapeutic use is part of the cultural memory of the residents of this municipality.